Oral health professionals screening for undiagnosed type-2 diabetes and prediabetes: the iDENTify study - Rodrigo Mariño; Andre Priede; Michelle King; Geoffrey G. Adams; Maria Sicari; Mike Morgan (BMC Endocrine Disorders, 2022)
Abstract Background As part of an evaluation of an oral healthcare practice-based model that identifies patients with prediabetes or type-2 diabetes, this study reports on the proportion of patients identified with clinically confirmed type-2 diabetes (T2D)/prediabetes and barriers of implementation of the model. Methodology Urban and rural oral healthcare practices were invited to participate. Participating practices invited eligible patients to participate in the screening program using the Australian Type-2 Diabetes Risk Assessment Tool (AUSDRISK). Participants were categorised as low, intermediate, or high-risk for prediabetes/T2D. Patients in the intermediate or high-risk category were referred to their General Medical Practitioner (GP) for further investigation. Results Fifty-one oral healthcare practices and 76 Oral Health Professionals (OHP) participated (60 Dentists, 8 Dental Hygienists, 8 Oral Health Therapists). 797 patients were screened; 102 were low-risk; 331 intermediate-risk; and 364 high-risk for T2D. Of the 695 participants in the intermediate or high-risk groups, 386 (55.5%) were referred to their GP for T2D assessment. Of them, 96 (25.0%) results were returned to OHPs. Of the returned results, six were (6.3%) diagnosed with pre-T2D. Conclusion Patients found to have undiagnosed T2D/prediabetes (6.3%) were within the expected range reported in the literature. Findings indicate that identifying individuals at an elevated risk of having or developing T2D is effective, feasible and could be incorporated into oral healthcare settings. However, this integration may require additional OHPs training and education to ensure that patients at elevated risk of T2D are referred for further assessment.